2016
DOI: 10.1017/mor.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Labor Unrest and Incipient Collective Bargaining in China

Abstract: In this paper, we argue that both labor unrest and collective bargaining are increasing in China. Using McAdam's political process theory, we argue that Chinese workers are striking more and offensively in support of their economic demands. We identify the state's interests in promoting collective bargaining, and through an analysis of union and employers organizations, attempt to predict the future trajectory of collective bargaining in China. Using new data about strikes, we confirm our argument that strikes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
0
32
0
4
Order By: Relevance
“…27 Some studies classify as collective bargaining collective consultations or tripartite and branch bargaining driven from the top of the ACFTU and in which workers are at most tangentially involved. 28 I do not consider such experiences to be genuine collective bargaining as defined above. I focus solely on negotiations initiated by workers, which involve workers directly throughout the process, and which imply a rebalancing of power relations, that is, processes at the enterprise level.…”
Section: The Practice Of Bargaining In An Authoritarian Statementioning
confidence: 99%
See 1 more Smart Citation
“…27 Some studies classify as collective bargaining collective consultations or tripartite and branch bargaining driven from the top of the ACFTU and in which workers are at most tangentially involved. 28 I do not consider such experiences to be genuine collective bargaining as defined above. I focus solely on negotiations initiated by workers, which involve workers directly throughout the process, and which imply a rebalancing of power relations, that is, processes at the enterprise level.…”
Section: The Practice Of Bargaining In An Authoritarian Statementioning
confidence: 99%
“…By basically performing the job that the trade unions should have, labour NGOs were perceived as competitors rather than potential partners as trade unions contributed to their own marginalization through their lack of response. The crackdown may also have been spurred by the financial cost of increasingly frequent and successful collective bargaining in a context of economic slowdown, movement of capital from the Pearl River Delta 76 and efforts by local authorities to prevent factories from relocating: in the last five years, the Panyu Centre -which was a key target of the December 2015 crackdown -has helped workers obtain nearly RMB 200 billion in wages, lay-off compensation, social insurance contributions and other benefits. 77 However, the story of collective bargaining in Guangdong Province is not yet over, thanks to activists' commitment.…”
Section: Negotiating Authoritarianism and Its Limitsmentioning
confidence: 99%
“…Further studies address the factors contributing to enterprise resilience under adverse conditions (Branzei & Abdelnour, 2010;Sinkovics et al, 2014), with studies on entrepreneurship investigating the internationalization of immigrant entrepreneurs (Sui, Morgan, & Baum, 2015) and the export orientation of entrepreneurial activity (Terjesen & Hessels, 2009). Further areas relate to public-private partnerships and collaboration with NGOs (George, Rao-Nicholson, Corbishley, & Bansal, 2015;Gifford & Kestler, 2008), criminal enterprises (Gillespie & McBride, 2013;Wood & da Costa, 2015), humanitarian logistics (Hirschinger, Moser, Schaefers, & Hartmann, 2016), social upgrading in GVCs (Khattak, Haworth, Stringer, & Benson-Rea, 2017;Lee & Gereffi, 2015), and unionization and collective bargaining (Kuruvilla & Zhang, 2016).…”
Section: Business Models and Entrepreneurship In Developing Marketsmentioning
confidence: 99%
“…The key foci of scholarly attention with respect to collective bargaining during this period has been the state's interest in fostering the growth of collective bargaining; the quantitative increase in collective contracts; the varying quality of these agreements; and the collective bargaining developments across China and their implications for the future of labor voice. Kuruvilla and Zhang (2016) suggested that the state fostered the development of collective bargaining through three separate initiatives: a change in the role of the Ministry of Human Resources and Social Security (MOHRSS) to make it more responsible for collective bargaining; the inclusion of provisions for collective negotiations in the new labor laws of the 2007 to 2010 period (discussed above); and, most important, the instructions to the ACFTU to increase union organizing and collective bargaining coverage across the country, with annual organizing targets. An institutional explanation for the state's actions is that it was relying on Webb and Webb's (1897) notions of dealing with labor conflict through both minimum standards legislation and collective bargaining-although the prohibition of an independently chosen union somewhat militates against their objective.…”
Section: Collective Bargaining 2006 To 2015mentioning
confidence: 99%
“…Whatever the state's interests, its encouragement of collective bargaining has been successful in quantitative terms, as the number of collective bargaining agreements increased at an annual rate of 19.30%, from 251,794 agreements in 2005 to 6,078,483 agreements in 2010. By 2010, these agreements covered more than 75 million workers (Kuruvilla and Zhang 2016). Nominal wages also grew at an annual average of 13 to 14% between 2005 and 2012.…”
Section: Collective Bargaining 2006 To 2015mentioning
confidence: 99%